2016
DOI: 10.1007/s10549-016-4039-x
|View full text |Cite
|
Sign up to set email alerts
|

A model for individualized risk prediction of contralateral breast cancer

Abstract: Purpose Patients diagnosed with invasive breast cancer (BC) or ductal carcinoma in situ are increasingly choosing to undergo contralateral prophylactic mastectomy (CPM) to reduce their risk of contralateral breast cancer (CBC). This is a particularly disturbing trend as a large proportion of these CPMs are believed to be medically unnecessary. Many BC patients tend to substantially overestimate their CBC risk. Thus, there is a pressing need to educate patients effectively on their CBC risk. We develop a CBC ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 43 publications
2
51
0
Order By: Relevance
“…CBC remains a major concern for women diagnosed with a first breast cancer, but risk is variable and effective risk prediction models are needed. Such models would be essential in making decisions about prophylactic contralateral mastectomy [ 10 ]. Given that annual mammography to screen for new breast primaries in the contralateral breast is recommended for women with a first breast cancer diagnosis [ 5 ], it is reasonable to consider MD for inclusion in CBC prediction models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBC remains a major concern for women diagnosed with a first breast cancer, but risk is variable and effective risk prediction models are needed. Such models would be essential in making decisions about prophylactic contralateral mastectomy [ 10 ]. Given that annual mammography to screen for new breast primaries in the contralateral breast is recommended for women with a first breast cancer diagnosis [ 5 ], it is reasonable to consider MD for inclusion in CBC prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence showing that higher MD at the time of a diagnosis of ductal carcinoma in situ (DCIS) is associated with increased CBC risk [ 6 8 ]. Two large studies including women with both DCIS and invasive cancer observed higher rates of any second breast primary [ 9 ] or CBC [ 10 ] in women with heterogeneously dense or extremely dense Breast Imaging Reporting and Data System (BI-RADS) categories before diagnosis compared to women with almost entirely fatty breasts. Similar results were observed in women with invasive breast cancer only [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents the case-control distributions for the two cohorts together with those of BCSC and SEER data on which CBCRisk was built [10]. The proportion of cases in both the cohorts are smaller than those in BCSC and SEER.…”
Section: Resultsmentioning
confidence: 99%
“…The women in the JH cohort tend to be associated with higher risks of CBC compared to those in the MDA cohort, thereby leading to an increased value of E for that cohort. For example, the “pure DCIS” and “mixed invasive/DCIS” categories of first BC type are associated with higher risks of CBC compared to the “pure invasive” category [10]; and the JH cohort is 60% “pure DCIS” or “mixed invasive/DCIS,” whereas the MDA cohort is 98% “pure invasive.” Likewise, unknown family history of BC is associated with a higher risk compared to no family history and the JH cohort has 96% unknown family history while the MDA cohort has 83% no family history. Moreover, unknown status of anti-estrogen therapy is associated with a higher risk compared to having the therapy; and the JH cohort has 63% with unknown status whereas in the MDA cohort 70% have anti-estrogen therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation